Sudden Cardiac Arrest and Malignant Ventricular Tachycardia in an 8-Year-Old Pediatric Patient Who Has Hemolytic Uremic Syndrome Associated with Shiga Toxin-Producing Escherichia coli - Yesilbas, Osman; Yozgat, Can Yilmaz; Akinci, Nurver; Talebazadeh, Faraz; Jafarov, Uzeyir; Guney, Abdurrahman Zarif; Temur, Hafize Otcu; Yozgat, Yilmaz (Journal of Pediatric Intensive Care, 2020)
Gastrointestinal, neurological, pancreatic, hepatic, and cardiac dysfunction are extrarenal manifestations of hemolytic uremic syndrome associated with Shiga toxin-producing Escherichia coli (STEC-HUS). The most frequent cause of death for STEC-HUS is related to the central nervous system and cardiovascular system. Cardiac-origin deaths are predominantly related to thrombotic microangiopathy-induced ischemia and the immediate development of circulatory collapse. STEC-HUS cardiac related deaths in children are rare with only sporadic cases reported. In our literature search, we did not come across any pediatric case report about STEC-HUS causing sudden cardiac arrest and malignant ventricular tachycardia (VT). Herein, we report the case of an 8-year-old female child with a typical clinical manifestation of STEC-HUS. On the seventh day of pediatric intensive care unit admission, the patient had a sudden cardiac arrest, requiring resuscitation for 10 minutes. The patient had return of spontaneous circulation with severe monomorphic pulsed malignant VT. Intravenous treatment with lidocaine, amiodarone and magnesium sulfate were promptly initiated, and we administered multiple synchronized cardioversions, but VT persisted. Furthermore, we were not able to ameliorate her refractory circulation insufficiency by advanced cardiopulmonary resuscitation. Thus, inevitably, the patient lost her life. This case illustrates the need for aggressive management and the dilemma that pediatric critical care specialists, cardiologists, and nephrologists have to face when dealing with STEC-HUS that is worsened by a sudden cardiac arrest accompanied with VT.
Keywords: intracranial hemorrhage; ventricular tachycardia; hemolytic uremic syndrome; cardiopulmonary resuscitation; pediatric intensive care unit